(untitled) (Revista Española de Fisiología, 1997)
Fish react to handling and capture with a burst of exercise that affects them deeply. The present study examines the effect of such severe exercise and the time course of recovery on the hematology (including spleen response) and metabolism of a population of cultured rainbow trout. Exercise was induced by continuous chasing for 5 min when the trout showed signs of exhaustion. Such exercise led to spleen contraction and an increase in haematocrit values. Carbohydrates were mobilized and anaerobic glycolysis produced lactate without significant effect on lipid metabolism. The conclusion is reached that the respiratory properties of rainbow trout blood do not change following severe exercise, while muscle anaerobic metabolism is slightly activated as deduced from the fast and short lactacidemia observed, which may have been related to a reduced stressing component, as the exercise was performed in the same environment in which the fish were reared.